EFEKTIFITAS PELAYANAN PERIZINAN PADA KANTOR BADAN PELAYANAN PERIZINAN TERPADU DAN PENANAMAN MODAL (BPPTPM) KABUPATEN KUTAI BARAT - Nina, Anton (PREDIKSI, 2016)
Badan Pelayanan Perizinan Terpadu dan Penanaman Modal Kabupaten Kutai Barat held an organized pattern One Of Licensing Services as known One Stop Service. Based on the Regulation of the Minister of Home Affairs Number 24Tahun 2006 on Guidelines for the Implementation of One Stop Licensing Services, then the activities of provision of services licensing and non-licensing process is started from a request to stage the release or publication of a document is done by single door, for a good, fast, cheap, transparent, certain, affordable public services. In the Decree of the Minister of Administrative Reform No. 63 / KEP / M.PAN / 7/2003, which meant One Stop is a pattern of service are maintained in one place that includes various types of services that have relevance to the process and serviced through a single door. This study aims to determine the effectiveness of Badan Pelayanan Perizinan Terpadu dan Penanaman Modal and Kutai Barat, provide input to Badan Pelayanan Perizinan Terpadu dan Penanaman Modal and Kutai Barat for more attention to the service of making licensing and non-licensing, to make the One Stop service more effective. Based on the results of research and discussion that has been described in previous discussion that the effectiveness Badan Pelayanan Perizinan Terpadu dan Penanaman Modal (BTPPM) Kutai Barat, it can be concluded that the service of making licensing in BPTPM Kutai Barat has been quite effective. Indicators used to measure the effectiveness of licensing services in BPTPM Kutai Barat is the achievement of objectives and the satisfaction of the group’s target.